Penyuluhan tiga bidang program kemitraan wilayah pada kelompok petani perhutanan sosial penanam kentang di Desa Gerlang Kabupaten Batang (Explanation of three areas of regional partnership program at potato groups social forestry farmers in Gerlang Village, Batang District) - Hersoelistyorini, Wikanastri; Iriyanto, Setia; Sukowiyono, Sukowiyono; Nurrahman, Nurrahman; Nurcahyono, Nurcahyono; Ethica, Stalis Norma; Suyanto, Agus; Aminah, Siti (Buletin Pengabdian, 2022)
The purpose of this service was to provide counseling, training, and technical guidance in three areas of the partnership program (food technology, economy, and health) to potato farmers in the village. In the field of food technology, counseling included how to process potatoes into flour, chips, and sticks. Counseling in the field of economics focused on the importance of entrepreneurship supported by e-commerce in marketing processed potatoes. Health education in the form of video screenings and distribution of posters about the dangers of open defecation (BABS). The results of the activity obtained information that the communitys understanding of how to wash hands properly was good, but needed guidance on healthy toilet standards. Extension activities in the health sector had a positive impact in increasing knowledge about the correct way to defecate. Counseling in the field of food technology and economics encouraged the growth of seven groups for introducing food technology and e-commerce in Gerlang Village.